Influence of Copper on А1 to L1₀ Phase Transformation in Nanoscale Fe₅₀Pt₅₀ Films - Makogon, Yu.M.; Pavlova, O.P.; Sidorenko, S.I.; Verbytska, T.I.; Verbytska, M.Yu.; Fihurna, O.V. (Металлофизика и новейшие технологии, 2015)
By the methods of materials science, the effect of intermediate Cu layer with low surface energy (≅1.83 J/m²) (top, intermediate, and underlayer) in [Fe₅₀Pt₅₀(15 nm)/intermediate Cu(7.5 nm) layer/Fe₅₀Pt₅₀ (15 nm)]n (where n=1,2), top Cu(7.5 nm) layer/Fe₅₀Pt₅₀(15 nm) and Fe₅₀Pt₅₀ (15 nm)/underlayer Cu(7.5 nm) film compositions on SiO₂(100 nm)/Si(001) substrates on diffusion phase-formation processes and L1₀ phase formation, its structure, and magnetic properties at annealing in vacuum is studied. The film compositions are prepared by magnetron sputtering on thermally oxidized SiO₂ layer by thickness of 100 nm on monocrystalline Si(001) substrate. Subsequent heat treatment is carried out at high vacuum of 1.3∙10⁻³ Pa in the 300—900°C temperature range during 30 s at each temperature. As determined, the chemically disordered A1(FePt) phase is formed in all as-deposited films. The formation of chemically ordered L1₀(FePt) phase in [Fe₅₀Pt₅₀(15 nm)/Сu(7.5 nm) intermediate layer/Fe₅₀Pt₅₀(15 nm)]n films (where n=1,2) with intermediate layers takes place during annealing at 700°C and is accompanied by sharp coercivity increase, which also rises after subsequent high-temperature annealing. In the films with top copper layer, the temperature of L1₀(FePt) phase formation rises up to 900°C. In the films with copper underlayer, the formation of L1₀(FePt) phase is not detected by X-ray analysis, but small coercivity increasing after annealing within the temperature range of 800—900°C can testify that ordering processes proceed. Методами фізичного матеріялознавства вивчено вплив додаткового шару Cu з низькою поверхневою енергією (≅1.83 Дж/м²) (верхнього, проміжного і підшару) в плівкових композиціях [Fe₅₀Pt₅₀(15 нм)/проміжний шар Сu(7,5 нм)/Fe₅₀Pt₅₀(15 нм)]n (де n=1,2), верхній шар Сu(7,5 нм)/Fe₅₀Pt₅₀(15 нм) і Fe₅₀Pt₅₀(15 нм)/підшар Сu(7,5 нм) на підложжях SiO₂(100 нм)/Si(001) на процеси дифузійного фазоутворення, формування фази L1₀ та її структурні й магнетні властивості при відпалах у вакуумі. Плівкові композиції одержано методом магнетронного осадження на термічно окиснене (шар SiO₂товщиною 100 нм) підложжя монокристалічного Si(001). Наступне термічне оброблення тривалістю у 30 секунд виконувалося у високому вакуумі 1,3∙10⁻³ Па в температурному інтервалі 300—900°C. Встановлено, що в усіх плівках після осадження формується хемічно невпорядкована фаза A1(FePt). Формування хемічно впорядкованої фази L1₀(FePt) у плівках з проміжними шарами міді [Fe₅₀Pt₅₀(15 нм)/проміжний шар Сu(7,5 нм)/Fe₅₀Pt₅₀(15 нм)]n (де n=1,2) відбувається в ході відпалу при температурі 700°C і супроводжується різким збільшенням коерцитивної сили, яка зростає також і після наступних високотемпературних відпалів. У плівках з верхнім шаром міді температура формування фази L1₀(FePt) підвищується до 900°C. У плівці з підшаром міді утворення фази L1₀(FePt) рентґенографічно не встановлено, але невелике збільшення коерцитивної сили після відпалів в інтервалі температур 800—900°C може свідчити про перебіг процесів упорядкування. Методами физического материаловедения изучено влияние дополнительного слоя Cu с низкой поверхностной энергией (≅1.83 Дж/м²) (верхнего, промежуточного и подслоя) в плёночных композициях [Fe₅₀Pt₅₀(15 нм)/ промежуточный слой Cu(7,5 нм)/Fe₅₀Pt₅₀(15 нм)]n (где n=1,2), верхний слой Cu(7,5 нм)/Fe₅₀Pt₅₀(15 нм) и Fe₅₀Pt₅₀(15 нм)/подслой Cu(7,5 нм) на подложках SiO₂(100 нм)/Si(001) на процессы диффузионного фазообразования, формирование фазы L1₀ и её структурные и магнитные свойства при отжигах в вакууме. Плёночные композиции получены методом магнетронного осаждения на термически окислённую (слой SiO₂ толщиной 100 нм) подложку монокристаллического Si(001). Последующая термическая обработка длительностью 30 секунд выполнялась в высоком вакууме 1,3∙10⁻³ Па в температурном интервале 300—900°C. Установлено, что во всех плёнках после осаждения формируется химически неупорядоченная фаза A1(FePt). Формирование химически упорядоченной фазы L1₀(FePt) в плёнках с промежуточными слоями меди [Fe₅₀Pt₅₀(15 нм)/промежуточный слой Cu(7,5 нм)/Fe₅₀Pt₅₀(15 нм)]n (где n=1,2) происходит в процессе отжига при температуре 700°C и сопровождается резким увеличением коэрцитивной силы, которая возрастает также и после последующих высокотемпературных отжигов. В плёнках с верхним слоем меди температура формирования фазы L1₀(FePt) повышается до 900°C. В плёнке с подслоем меди образование фазы L1₀(FePt) рентгенографически не установлено, но небольшое увеличение коэрцитивной силы после отжигов в интервале температур 800—900°C может свидетельствовать о прохождении процессов упорядочения.